Structure and decay of the highly mixed 132+ states in 171Er - kreiner, A. J.; Bond, P. D.; Baktash, C.; Barrette, J.; Thorn, C. E.; Collins, M. T. (The American Physical Society, 1982)
Fil: kreiner, A. J. Comisión Nacional de Energía Atómica; Argentina